2010
DOI: 10.1016/j.ajog.2010.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Long-term physical and neurologic development in newborn infants with isolated single umbilical artery

Abstract: OBJECTIVE This study compared birth parameters and the longitudinal course in physical and neurologic development between children with 2 and 3 vessel umbilical cords. STUDY DESIGN Our study of the Collaborative Perinatal Project included singletons of at least 24 weeks’ gestation with single umbilical artery at birth and no identifiable congenital anomalies. Demographics that were collected included maternal age, race, smoking status, and socioeconomic index. Delivery data included gestational age, birth-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 18 publications
2
32
2
Order By: Relevance
“…During prenatal fetal abnormality screening, it is recognized as a soft marker of congenital structural malformation, chromosomal defect, fetal growth restriction, premature and low birthweight . Extremely high risk of structural abnormality in all major organ systems, including abnormality in genitourinary, musculoskeletal, gastrointestinal, cardiovascular and central nervous systems, was detected in SUA fetus, which was higher than those with double umbilical artery …”
Section: Introductionmentioning
confidence: 91%
“…During prenatal fetal abnormality screening, it is recognized as a soft marker of congenital structural malformation, chromosomal defect, fetal growth restriction, premature and low birthweight . Extremely high risk of structural abnormality in all major organ systems, including abnormality in genitourinary, musculoskeletal, gastrointestinal, cardiovascular and central nervous systems, was detected in SUA fetus, which was higher than those with double umbilical artery …”
Section: Introductionmentioning
confidence: 91%
“…Compensatory mechanisms allow increase in blood flow through the single artery in order to meet the demands of fetal growth and development throughout pregnancy. 3 Although several studies have reported diminished fetal growth in these pregnancies, [4][5][6][7][8][9][10][11][12] others have not shown differences. [13][14][15] These contradictory findings may be attributed to diverse methodological differences in the published literature.…”
Section: Introductionmentioning
confidence: 99%
“…Additional clinical relevance of ISUA was also evaluated after birth in a prospective cohort by Chetty-John et al 10 No significant differences in physical growth and neurological development were observed. There was also no evidence of increased need for admission to neonatal intensive care units (Bombrys et al).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is well known, umbilical cords are an important channel for fetuses and mothers to exchange oxygen, nutrients and waste materials. Some scholars believe that an SUA might cause atrophy and extensive fibrin accumulation in certain areas of the placenta, chorionic villus edema or reduced blood flow in the fetal circulation, which will induce secondary hypoxia, hypogenesis and other conditions, such as fetal growth restriction . Other scholars believe that there is no significant difference in neonatal outcome when the SUA is found without other anomalies .…”
Section: Discussionmentioning
confidence: 99%